Effect of Different Wheatstone Bridge Configurations on Sensitivity and Linearity of MEMS Piezoresistive Intracranial Pressure Sensors - Mohamad, Mazita; Soin, Norhayati; Ibrahim, Fatimah (Journal of Electronic Voltage and Application, 2020)
Monitoring of intracranial pressure for traumatic brain injured patients is very critical.  Many intracranial pressure monitoring systems use the MEMS piezoresistive pressure sensor to measure the signal.  The piezoresistive pressure sensor is very sensitive to temperature change.  Hence, the Wheatstone bridge circuit is normally employed in this type of sensor to lessen the effect of temperature variation.  This paper presents the effect of using different configurations of Wheat-stone bridge on the sensitivity and linearity performances of the piezoresistive intracranial pressure sensor.  Six designs comprise of 3-turns meander shaped piezoresistors ranging from full-bridge to quarter-bridge were simulated using COMSOL Multiphysics.  Based on the simulation results, the number and position of active piezoresistors were found to greatly influence the sensitivity of the sensor.  The latter also influenced the sensorsâ€™ linearity error.  The active perpendicular piezoresistor produced the higher change in resistance which gave rise to higher sensitivity, while at the same caused the higher nonlinearity performance.  Overall, the piezoresistive intracranial sensor comprises of full-bridge Wheat-stone circuit produces the highest sensitivity and medium linearity.